2008
DOI: 10.1038/leu.2008.272
|View full text |Cite
|
Sign up to set email alerts
|

PD-1/PD-L1 expression in human T-cell leukemia virus type 1 carriers and adult T-cell leukemia/lymphoma patients

Abstract: Adult T-cell leukemia/lymphoma (ATLL) develops after infection with human T-cell leukemia virus-1 (HTLV-1) after a long latency period. The negative regulatory programmed death-1/ programmed death-1 ligand 1 (PD-1/PD-L1) pathway has been implicated in the induction of cytotoxic T-lymphocyte (CTL) exhaustion during chronic viral infection along with tumor escape from host immunity. To determine whether the PD-1/ PD-L1 pathway could be involved in the establishment of persistent HTLV-1 infections and immune evas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
131
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(139 citation statements)
references
References 44 publications
4
131
1
1
Order By: Relevance
“…Our findings contrast with what has been shown in HTLV-1 infection, where a marked increase of PD-1 expression could be found both in asymptomatic carriers and in patients with ATLL (43). Although these findings would not suggest immune exhaustion of virus-specific CTLs in HTLV-2 infection, this will require further studies.…”
Section: Figurecontrasting
confidence: 55%
“…Our findings contrast with what has been shown in HTLV-1 infection, where a marked increase of PD-1 expression could be found both in asymptomatic carriers and in patients with ATLL (43). Although these findings would not suggest immune exhaustion of virus-specific CTLs in HTLV-2 infection, this will require further studies.…”
Section: Figurecontrasting
confidence: 55%
“…Primary ATL cells in 21.7% of ATL patients expressed PD-L1, while elevated expression was not observed in cells from ACs. 43) Finally, in functional studies we observed that an anti-PD-L1 antagonistic antibody upregulated HTLV-1-speciˆc CD8+ T-cell response (Fig. 2B).…”
Section: Decreased Frequency and Function Of Htlv-1-specific Ctl In Atlmentioning
confidence: 97%
“…These results suggest that decreased frequency, diversity, and function of anti-HTLV-1 Tax CD8+ T-cell clones may be one of the risks of ATL development. 32,33) patients may be involved in progression from HTLV-1 carrier to ATL, and also contribute to the aggressiveness of this disease, which is refractory to treatment.…”
Section: Decreased Frequency and Function Of Htlv-1-specific Ctl In Atlmentioning
confidence: 99%
“…We have reported PD-1 expression on Tax-specific CTLs may indicate Tax-specific T cell exhaustion [51].…”
Section: Immunological Impairment Of Htlv-1 Specific T Cellsmentioning
confidence: 96%